Genetic variation and structure in natural populations of Melica ciliata and M. transsilvanica (Poaceae) as indicated by AFLP markers - Szczepaniak, Magdalena; Cieślak, Elżbieta (Biodiversity: Research and Conservation, 2006)
Melica ciliata L. and M. transsilvanica Schur are rare species in the Polish flora and reach here northern limit of their continuous range. A fluorescence-labeled Amplified Fragment Length Polymorphisms (AFLPs) DNA profiling method was used to measure genetic diversity and relationships between and within natural populations of M. ciliata and M. transsilvanica from central Europe. Analysis of molecular variance (AMOVA) revealed the significant genetic diversity (70.77%, p<0.002) between these species. At the intraspecific level, most genetic diversity resided between populations of both M. ciliata and M. transsilvanica (FST=0.84 and 0.94, respectively), that indicates a high level of inbreeding. The obtained low level of AFLP variation and the high FST values suggest the weakness or absence of gene flow among populations of these species, and maintenance the separate, local gene pool in each population. Fragmented landscapes, the putative self-pollinated breeding system and genetic drift, particularly in small size populations, may perform an important role in shaping the genetic diversity of the populations and the genetic structure of M. ciliata and M. transsilvanica.